Persepsi manajer terhadap pengukuran kinerja berbasis human resource scorecard - Subur, Rahmat (Jurnal Manajemen, 2018)
The analysis conducted in this research is descriptive qualitative analysis based on observations made based on company data and information and reinforced by interviews and focus group discussions to get an idea of the opportunity to apply the design of performance measurement indicators based on Human Resources Scorecard. The results of the analysis of strategy objectives at PT. Cahaya Sakti Furintraco owned in the form of Corporate Philosophy, Vision, Mission and Annual Range Plan can be the foundation of the organization to achieve the ideals to maintain the continuity of the company’s way. An important stage that should be done company especially the implementation stage is realized by the execution of the spirit of values contained in the company’s philosophy, vision and mission is preceded by leaders as agents of change. Meanwhile, the strategy objectives of the existing human resources division have not yet played a role, due to the lack of socialization and the absence of programs in accordance with the current conditions due to incompatibility of views from each stakeholder. The design of the measurement of existing performance indicators has not yet implemented Human Resources Scorecard based performance indicators because there is no sponsorship to make changes to the performance measurement system from existing to new performance measurement systems. Analisis yang dilakukan dalam penelitian adalah analisis kualitatif deskriptif berdasarkan pengamatan yang dilakukan bersumber pada data dan informasi perusahaan serta diperkuat dengan wawancara dan diskusi kelompok terarah (Focus Group Discussion) untuk memperoleh gambaran peluang penerapan perancangan indikator pengukuran kinerja berbasis Human Resources Scorecard. Hasil analisis mengenai sasaran strategis di PT. Cahaya Sakti Furintraco yang dimiliki berupa Filosofi, Visi, Misi dan Annual Range Plan perusahaan dapat menjadi landasan organisasi untuk mencapai cita -cita untuk mempertahankan kelangsungan jalannya perusahaan. Tahap penting yang harus dilakukan perusahaan terutama tahap penerapan yang diwujudkan dengan dijalankannya semangat nilai-nilai yang terkandung dalam filosofi, visi dan misi perusahaan didahului oleh para pemimpin sebagai agen perubahan. Sementara itu sasaran strategis divisi SDM yang ada saat ini belum berperan, karena kurangnya sosialisasi dan belum adanya program yang sesuai dengan kondisi saat ini akibat adanya ketidaksesuaian pandangan dari masing-masing pemangku kepentingan. Perancangan pengukuran indikator kinerja yang ada belum menerapkan indikator kinerja berbasis Human Resources Scorecard karena belum adanya sponsor untuk melakukan perubahan sistem pengukuran kinerja dari yang ada ke sistem pengukuran kinerja baru.